, ; The rouble crisis and the Russian grain export controls - Thomas Glauben; Linde Johanna Götz; Ulrich Koester (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2015)
C 1- 2015 . . , . , , , , , , , . . , , , . . , , . – – Since 1 February 2015, an additional tax has been levied on Russian wheat exports to reduce the recently strongly rising wheat exports. The aim is to dampen further increases in the already high domestic wheat prices and to stabilise bread prices. However, recent experiences in various countries as Ukraine, Kazakhstan, Serbia, and Russia show that grain export restrictions do little if anything to moderate bread prices. Poor people will also fail to profit from this governmental market intervention. Instead, grain export barriers will disconnect the Russian grain producers from the international markets while necessary investments in the grain sector decline which decreases food security. This form of protectionism by the government is ample cause for serious concern. Considering the current downswing in the Russian economy, the destabilisation of the strategically important grain sector will most certainly not improve the investment climate in Russia.
urn:nbn:de:gbv:3:2-60711
Keywords: 330